Implementation of the Scaffolding Method in Improving Learning Outcomes on the Material on the Characteristics of the Prophet at State Elementary School 096466 Pematang Gajing - Susanti, Eva; Saragih, Desi Asmaini; Murianto; Lubis, Affridha Yani; Rahimah (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to analyze the effectiveness of the scaffolding method in improving student learning outcomes on the material about the characteristics of the prophet at SDN 096466 Pematang Gajing Scaffolding is a learning method that provides support to students gradually as they learn. This support can be in the form of content, processes, and learning strategies that provide gradual guidance to students until they can understand the material independently. In this study, the method used was classroom action research (CAR) by adjusting the level of teaching according to students' cognitive abilities. Data were collected through observation, learning outcome tests, and interviews to assess the development of student understanding before and after the implementation of scaffolding. The results showed that the scaffolding method contributed positively to improving students' understanding of the material about the characteristics of the prophet. The support provided by the teacher by providing direction and support by providing direct and easy-to-understand examples and using fun teaching materials so as to help students build a good understanding in order to stimulate students to be able to understand and solve their own problems. In addition, students become more active in the learning process and are able to learn and instill the characteristics of the prophet in everyday life. In conclusion, the implementation of the scaffolding method systematically and continuously can improve student learning outcomes, especially in materials related to moral values. Therefore, this method can be an effective learning alternative at the elementary school level